Periphyton Community Structure on Natural and Artificial Substrates in the Namu Sira-Sira River, Langkat Regency, North Sumatra - Fathia Azzahra; Melfa Aisyah Hutasuhut; Zahratul Idami (Universitas Labuhanbatu, 2025)
Periphyton is one of the biotic components, living attached to various substrates has an important role in providing primary productivity of waters. The purpose of this study was to determine the identification of species, the structure of the periphyton community in natural and artificial substrates, the water quality of the Namu Sira-sira River in Langkat Regency. The data collection method was carried out using the